An investigation of the underlying mechanisms of overtraining in a natural experimental model - Koning, J.; ten Haaf, T.; van Staveren, S.; Roelands, B.; Foster, C.; Piacentini, M. F.; Meeusen, R. (Journal of Science and Cycling, 2015)
According to the definitions described in the literature `overtraining` is used as a verb, a process of intensified training with possible outcomes of functional overreaching [FOR], nonfunctional overreaching [NFOR] or overtraining syndrome [OTS] (Halson 2004; Urhausen 2002). The distinction between (N)FOR and OTS can only be made retrospectively when the time course of recovery can be viewed in context. In the case of OTS, the recovery can take a very long time, and can end an athlete`s season or even career. FOR is used by coaches to increase performance, but there is no clear line between FOR and maladaptive training responses (NFOR and in extreme severe cases OTS). The transition is gradual and includes a state of overreaching necessary to improve performance because of supercompensation of the affected physiological systems. If the balance between training load and recovery is inappropriate, this might result in persistent maladaptations to the training program. People with (N) FOR and OTS suffer from several psychological (e.g. mood disturbances (Morgan 1987)) and physical (e.g. performance decrement (Urhausen 1995)) symptoms. Since it seems impossible to treat NFOR/OTS (except rest), the emphasis must be on prevention and early diagnosis of NFOR/OTS.